Influence of calcium and ferric ions on the depression of chalcopyrite by CMC: Flotation performance and adsorption mechanism study. (30th June 2022) - Wang, Changtao; Liu, Runqing; Zhai, Qilin; Wu, Meirong; Jing, Nianwen; Xie, Feifei; Sun, Wei
Highlights: CMC physically adsorbed on chalcopyrite surface. Ca 2+ has barely effect on chalcopyrite flotation using CMC as depressant. Fe 3+ could enhance the depression of CMC towards chalcopyrite flotation but it was pH determined. After surface modification with Fe 3+, CMC chemisorption on chalcopyrite surface by bonding with Fe sites. Abstract: The inevitable presence of metal ions in the slurry significantly impacts the adsorption of organic depressants. In this study, the influence of Fe 3+ and Ca 2+ on the depression of chalcopyrite by carboxymethyl cellulose (CMC) was investigated. CMC slightly depressed chalcopyrite flotation, and the addition of Ca 2+ hardly impact its depression effect. However, the pre-treatment with Fe 3+ enhanced its depression effect severely at acid conditions, while this hydrophilic strengthening effect gradually disappeared under alkaline conditions. CMC physically attached to blank chalcopyrite surface, the surface modification with FeCl3 not only increased its adsorption capacity on chalcopyrite surface but also altered it from physical adsorption to chemical adsorption. Cu and Fe sites were not involved in CMC adsorption on blank chalcopyrite surface, and the strongly electrostatic repulsion hindered its adhesion under alkaline conditions. After surface modification with FeCl3, electrostatic repulsion was weakened, and Fe sites participated in the bonding with CMC molecule. Thus, chalcopyrite was strongly depressed. However, the contents of Fe 3+, Fe(OH) 2+ and Fe(OH)2 + on modified chalcopyrite were much less at strong alkaline conditions than acid conditions, which not favored CMC attachment.